2017
DOI: 10.3390/d9040052
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variants of Glutamine Synthetase and Glutamate Synthase Genes in a Collection of Durum Wheat and Association with Grain Protein Content

Abstract: Abstract:Wheat is one of the most important crops grown worldwide. Despite the fact that it accounts for only 5% of the global wheat production, durum wheat (Triticum turgidum L. subsp. durum) is a commercially important tetraploid wheat species, which originated and diversified in the Mediterranean basin. In this work, the candidate gene approach has been applied in a collection of durum wheat genotypes; allelic variants of genes glutamine synthetase (GS2) and glutamate synthase (GOGAT) were screened and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…Both glutamate synthase genes (GOGAT) and glutamate receptor-like (GLR) genes are key components in plant nitrogen metabolism and protein assimilation. GOGATs act in the first step of ammonium assimilation and glutamate synthesis [ 55 , 56 ]. GLRs are amino-acid sensors that have roles in nitrogen and carbon sensing, with additional functions in plant defense responses and adaptation to water deficit stress [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both glutamate synthase genes (GOGAT) and glutamate receptor-like (GLR) genes are key components in plant nitrogen metabolism and protein assimilation. GOGATs act in the first step of ammonium assimilation and glutamate synthesis [ 55 , 56 ]. GLRs are amino-acid sensors that have roles in nitrogen and carbon sensing, with additional functions in plant defense responses and adaptation to water deficit stress [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both GOGAT genes have found to be associated with GPC in durum wheat [35,36]. Furthermore, GS has been proposed as a candidate gene for improving NUE by several authors, and its relationship with GPC has also been widely reported [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 95%
“…durum genome browser (https ://d-gbrow se.inter omics .eu/), and only regions annotated as coding genes were considered for further analysis. The retrieved gene sequences were blasted against the available dataset of SNP marker sequences (Akhunov et al 2009;Wang et al 2014), as previously reported in other studies (Nigro et al 2017a(Nigro et al , b, 2019, and the ones aligned with at least 90% identity were considered as markers within the coding sequences of the gliadin genes. Additionally, SNPs markers were investigated and confirmed to locate within gene sequences by searching the variants table section reported for each gene in Ensembl Plants database (http://plant s.ensem bl.org/).…”
Section: Snp Discovery In Gliadins Genes In Tetraploid Wheatmentioning
confidence: 99%
“…The identified SNP markers were then screened in a collection of 240 accessions of tetraploid wheat genotypes (Triticum turgidum L., 2n = 4x = 28; AABB genome) (Laidò et al 2013). The collection was recently phenotyped for grain protein content (GPC) and genotyped for SNPs with the wheat 90 K Infinium iSelect array containing 81,587 gene-associated SNP markers, as reported by Nigro et al (2017aNigro et al ( , b, 2019.…”
Section: Snp Discovery In Gliadins Genes In Tetraploid Wheatmentioning
confidence: 99%